Bridging Halal Industry and Islamic Finance: Conceptual Review on the Internal Governance - Rahim, Norafni @ Farlina (School of Social Sciences, USM, 2017)
Halal has become a lifestyle and lucrative business. It is no longer a pure religious issue. Malaysia is a leader in this industry which championing in most of the areas particularly in Halal food, cosmetics and pharmaceuticals and also Islamic finance. Although these industries are under the same umbrella i.e. Halal and lies the under same Shariah principle, the internal governance system are different due to the nature and complexities of the industries. Malaysia Halal certification has achieve the world standard and become reference from other countries too. The Halal producers and manufacturers are required to comply with Trade Description Act, other Acts related with their nature of business, Malaysia Halal Standard (MS) and Manual for Halal Certification. To ensure the integrity of Halal operation, JAKIM has released the Halal Assurance Management System 2011 (HAS 2011). However, those policies are silent in the internal Halal governance framework. Compared to Islamic finance industry, they are governed by Shariah Governance Framework 2010. Thus, this study tries to review the governance system in Halal industries and Islamic finance and try to integrate them for solid better governance.